Nursing students and role modeled behavior while caring for LGBTQ + people: a cross-sectional, descriptive study - Emily E. Roy; Kristen D. Clark (BMC Nursing)
Abstract Background While efforts to improve the educational preparedness of nurses to care for lesbian, gay, bisexual, transgender, and queer (LGBTQ +) people have increased, the influence of role-modeled behaviors by healthcare professionals working with nursing students and recent graduates is not well understood. The purpose of this study is to describe the role-modeled behaviors of healthcare professionals observed by nursing students and recent graduates caring for LGBTQ + patients in clinical settings. Methods A cross-sectional, online survey was conducted. Recruitment of nursing students who had completed one or more clinical rotations or were recent graduates (≤ 2 years) was performed through university emails and social media. Items included measurement of stigmatizing attitudes, observed stigmatizing behaviors, and ability to provide inclusive/affirming care for LGBTQ + patients. Open-text items prompted participants to describe observed behaviors. Data were analyzed using descriptive statistics and Wilcoxon signed rank sum tests to evaluate differences between LGB (lesbian, gay, bisexual) and T + (transgender and gender diverse) subscales. Open-text responses were analyzed using thematic analysis to identify relevant themes. Results Participants (N = 73) had a low level of stigmatizing attitudes toward LGBTQ + people (M = 1.8, SD = 0.4), although higher stigmatizing attitudes toward T + people were reported (M = 3.0, SD = 0.2; Z = -7.254, p < .001). Half of the participants reported that they observed LGBTQ + stigmatizing behaviors role-modeled by two + healthcare professional roles; approximately one-third of participants personally engaged in one + LGBTQ + stigmatizing behaviors, most commonly toward T + people. Themes from participants’ examples of observed stigmatizing behaviors included: cis-heteronormative bias, non-affirmation of chosen name/pronouns, outing patients, and rejected competency. Conclusions The majority of participants described observing stigmatizing behaviors toward LGBTQ + people in clinical settings. Poorer attitudes and a higher frequency of stigmatizing behaviors observed towards T + people point to deficits in healthcare provided to T + people in particular. Efforts to address LGBTQ + stigma in healthcare should be expanded to include clinical settings to address role-modeled behaviors and socialization of nurses.